2015
DOI: 10.1002/clc.22411
|View full text |Cite
|
Sign up to set email alerts
|

Antithrombotic Regimens for Patients Taking Oral Anticoagulation After Coronary Intervention: A Meta‐analysis of 16 Clinical Trials and 9185 Patients

Abstract: The optimal antithrombotic regimen remains controversial in patients taking oral anticoagulation (OAC) undergoing coronary stenting. This study sought to compare efficacy and safety outcomes of triple therapy (OAC, aspirin, and clopidogrel) vs dual therapy (clopidogrel with aspirin or OAC) in these patients. We hypothesize OAC plus clopidogrel could be the optimal regimen for patients with indications for OAC receiving stent implantation. Medline, the Cochrane Library, and other Internet sources were searched … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 41 publications
0
19
0
Order By: Relevance
“…The use of clopidogrel as a single antiplatelet agent with warfarin after coronary stenting was compared with triple therapy, and although bleeding was reduced and no difference in ischemic outcomes was observed, the safety of this strategy is still debatable . A recent meta‐analysis from Gao et al reaffirms the risk of triple therapy and that alternative therapeutic regimens in PCI patients requiring oral anticoagulation may reduce bleeding without compromising safety …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of clopidogrel as a single antiplatelet agent with warfarin after coronary stenting was compared with triple therapy, and although bleeding was reduced and no difference in ischemic outcomes was observed, the safety of this strategy is still debatable . A recent meta‐analysis from Gao et al reaffirms the risk of triple therapy and that alternative therapeutic regimens in PCI patients requiring oral anticoagulation may reduce bleeding without compromising safety …”
Section: Discussionmentioning
confidence: 99%
“…There is, however, limited data supporting the routine prophylactic use of warfarin following anterior myocardial infarction (MI) complicated by LV dysfunction. Furthermore, concomitant warfarin and dual antiplatelet therapy (DAPT) is associated with a high risk of major bleeding . The 2013 American College of Cardiology/American Heart Association Guidelines, therefore, assigns a class IIb recommendation for the prophylactic use of warfarin in patients with STEMI and anterior apical akinesis or dyskinesis .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An individual patient-centered approach is preferred, as suggested in the European consensus document. 6 Nevertheless, in light of the findings from WOEST and registry data, 29 there seems to be an increasing amount of data supporting the use of dual therapy and OAC in selected AF patients rather than TT after PCI.…”
Section: Picard Et Al Triple Therapy For Af Patients Undergoing Pcimentioning
confidence: 99%
“…1,2) It has been confirmed that dual antiplatelet therapy (DAPT), including aspirin and a P2Y12 inhibitor, is not a good choice for these patients due to increased risk of ischaemic stroke and embolism complications. 3,4) Traditional triple therapy (vitamin K antagonist [VKA] + DAPT), which is recommended by current guidelines, 5,6) is associated with reduced ischaemic events but at the cost of the unacceptable risk of major bleeding. 3,4,7) Hence, VKA plus single antiplatelet therapy (SAPT), such as aspirin or clopidogrel, is also recommended to reduce the bleeding risk.…”
mentioning
confidence: 99%